Back Cover Image, Volume 41, Issue 6. Issue 6 (11th October 2021) - Çapcı, Aysun; Herrmann, Lars; Sampath Kumar, Halmuthur M.; Fröhlich, Tony; Tsogoeva, Svetlana B.
Abstract : The cover image is based on the Review Article Artemisinin‐derived dimers from a chemical perspective by Aysun Çapcı et al., https://doi.org/10.1002/med.21814 .